2020
DOI: 10.1186/s12944-020-01263-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post fermentation cooling patterns on fatty acid profile, lipid oxidation and antioxidant features of cow and buffalo milk set yoghurt

Abstract: Background: In the manufacturing of set yoghurt, after reaching 4.6 pH, post fermentation cooling is applied to stop the bacterial activity. Depending upon the required textural and flavor attributes, one phase and two phase cooling patterns are accordingly selected. In one phase cooling, temperature of the yoghurt is rapidly decreased below 10°C using blast freezing and then it is gradually dropped to 4-5°C. In two phase cooling, temperature of yogurt is rapidly decreased to less than 20°C and then it is grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Aloe Vera variety, harvesting stage, and juice extraction procedure can all be held responsible for the variance in Aloe Vera moisture content. Similar results were also reported by (Khan et al, 2020) who showed that the Aloe Vera gel contains 99% water and only about 1% total solids (dry matter). Additionally, while having a titratable acidity value that showed it was acidic, the juice had a very low fat content of only approximately (0.1) %.…”
Section: Chemical Analysis Of Aloe Vera Gel and Milksupporting
confidence: 90%
“…Aloe Vera variety, harvesting stage, and juice extraction procedure can all be held responsible for the variance in Aloe Vera moisture content. Similar results were also reported by (Khan et al, 2020) who showed that the Aloe Vera gel contains 99% water and only about 1% total solids (dry matter). Additionally, while having a titratable acidity value that showed it was acidic, the juice had a very low fat content of only approximately (0.1) %.…”
Section: Chemical Analysis Of Aloe Vera Gel and Milksupporting
confidence: 90%
“…During early storage, the generation of volatile compounds was slower, which was consistent with the POV and p ‐AV obtained in large yellow croaker oil. After 90 days, the number of volatile oxidation products greatly increased, due to the increased fatty acid oxidation, which produced more fatty acid off‐flavour and a strong oily smell (Khan et al ., 2020). When large yellow croaker oil was stored for 120 days, the generation of volatile flavour substances decreased, the reason might be that the fish oil quality deteriorated after oxidation and some oxidation products stopped reacting.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Michlová et al (2015), the content of vitamins A and E in goat's and sheep's milk subjected to high-temperature short-time (HTST) pasteurization decreased by 13% and 14%, and 23% and 14%, respectively. Khan et al (2020) found that the pattern of post-fermentation cooling had a significant influence on the antioxidant properties of yogurt and the concentrations of vitamins A and E. Both vitamins are highly sensitive to light. Vitamin A is degraded by photolysis, whereas vitamin E is degraded by photo-oxidation (Allwood and Martin 2000).…”
Section: Discussionmentioning
confidence: 98%